Unconventional irrigation water use in Turkey - Kanber R.; Ünlü M.; Koç D.L.; Önder D.; Cakmak E.H.; Tüzün M. (Non-conventional water use: WASAMED project, 2005)
In Turkey, water is a constraint to agricultural productivity in comparison with the extent of existing irrigable land resources, especially for Mediterranean, Centre and Southeast Anatolia regions, as they are arid and semi-arid regions. Interbasin water transfer is possible, but, would be very expensive and time consuming. For this reason, new water resources are required. Use of nonconventional water is considered to be among the best solutions. In the last decades, the studies were carried out for understanding the principles of such water for agricultural production such as determining the salinity threshold values and the effects of salinity on some properties of crop yield. The results showed that the salinity level of irrigation water decreased yield and qualities of all the crops. It is confirmed that resistance of crops to salinity level of irrigation water is not the same and vegetable crops are more sensitive than other crops.
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)